PLATELET ACTIVITY CORRECTION BY REGULAR PHYSICAL TRAINING IN YOUNG PEOPLE WITH HIGH NORMAL BLOOD PRESSURE - I. N. Medvedev; A. P. Savchenko (Российский кардиологический журнал, 2010)
In young people with high normal blood pressure, individually developed programme of physical training could normalise cardiovascular reactivity, lipid peroxidation, and platelet hemostasis parameters. Twelve-month physical training programme completely optimised platelet adhesion and aggregation in vitro, which was increased at baseline. This beneficial effect could be even stronger, if physical training continues.